An imbalance of COX level is not related to placental abruption. Issue 7 (10th May 2011) - Avagliano, Laura; Falleni, Monica; Marconi, Anna Maria; Bulfoni, Camilla; Prada, Arianna; Barbera, Antonino F; Doi, Patrizia; Bulfamante, Gaetano P
Abstract : Aims: Muscularised basal plate arteries (MA) or chorioamnionitis (CA) are often present in placental abruption. The aim of this study was to evaluate the placental expression of COX 1 and COX 2 in cases of placental abruption with MA or CA hypothesising that an imbalance in COX placental expression might be implicated in its pathogenesis. Methods: COX 1 and COX 2 placental immunostaining was analysed in 16 placentas with abruption (nine with MA, seven with CA), in 26 normal placentas and in 10 gestational age-matched MA or CA cases without abruption. Results: COX 1 and COX 2 protein expression was observed in all cases, both in placental abruption and in normal placentas. No differences in distribution of immunoreactivity were observed either between cases and controls or between MA and CA. The mean COX 1 ratio between COX-positive cells and all stromal cells was significantly lower in placental abruption with MA (0.14±0.05) when compared with cases with CA (0.35±0.06) and normal placenta (0.23±0.02; p<0.001). The mean COX 2 ratio was lower in placental abruption with MA than in normal placenta (0.09±0.06 vs 0.18±0.05: p<0.001). In contrast, no difference in COX 1 and COX 2 ratio was observed between MA cases with or without abruption and between CA cases with or without abruption. Conclusions: It is hypothesised that an imbalance of normal COX level may be present in cases with MA and CA but it is not related to placental abruption.